Paracas Un estado antiguo - Laura Lipe, Jhoan Jesús (Facultad de Ciencias Jurídicas y Políticas - Universidad Nacional del Altiplano de Puno, 2023)
Throughout the history of our country there were different cultural developments, in this essay we are going to take into account only one, this is the Paracas culture, one of the oldest in Peru, also known as the dominators of the desert since they originated in the north of our country. The aim of this essay will be based mainly on demonstrating that the Paracas were not just a simple cultural development or a group of inhabitants of ancient Peru, on the contrary, we seek to highlight that each behaviourthroughout their period of development had a very important purpose that would demonstrate why the Paracas were a state that had a great administrative and sovereign power throughout the extension of its territory.In the course of the essay, first of all, general aspects of the Paracas state are mentioned, such as its period of development in ancient Peru, its discovery, its marvellous textile technique expressed mainly in its ceremonial and funerary mantles, as well as its architectural constructions. The fundamental aspects for a society to establish itself as a state are established, which according to García Toma and Porrúa Pérez are Population, Territory and Authority or Political Power, then each element is developed in relation to Paracas.In relation to the Paracas Territory, the territorial extension that they managed to dominate is mentioned and, of course, their capital is defined. Regarding the political power, which was considered as a theocratic government, we will explain the origin and the influences they had for this development to take place. Last but not least, we will talk about the population as the basis for the formation of a state, taking into account the importance of the economic activities they carried out. Finally, taking these three points into account, we will come to the conclusion that the Paracas were a highly organised population in various aspects, which would lead us to consider them as a very well-developed state of Ancient Peru.